Analysis of Appraisive Characterization - Aschenbrenner, L. author. aut Link
XI, 230 p.
Keywords: The present work addresses itself to the question of the nature of appraisive concepts such as were the subject of investigation in The Concepts of Value* and The Concepts of Criticism. ** Many problems of prime importance in the theory of value could not be adequately treated there without diminishing the basic purpose of those studies which was above all to identify, classify and provide a general theoretical framework for the host of concepts with which we characterize and commend subjects of appraisal in all of the principal areas of human interest. The author might have forestalled the disappointment of some of his critics had he then explicitly promised to consider those problems at a later time. But his reluctance to promise what he might not be in a position to produce outweighed a keen awareness of what the problems are and of their evident seriousness. Although my treatment of such problems has only now been undertaken, in point of time my concern with them antedates by far the em pirical explorations of the two texts mentioned. Anyone who undertakes such a study is likely to have come under the in fluence of Professor Frank Sibley's 'Aesthetic Concepts't and of later develop ments in his analysis of certain appraisive concepts. What do such concepts mean and how do they mean9 These are the questions he treated in such a stimulating fashion.